Prioritising core competencies to enhance financial and strategic performance of Malaysian National Oil Company - Deven Sharma Krishnan (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
This study investigates the prioritisation of core competencies and competitive advantages with respect to financial and strategic performance. Through this study, interviews were conducted with business unit managers from the Malaysian National Oil Company to solicit their views about the company's core competencies, competitive advantages and its relationship to financial and strategic performance. The findings from the interviews were used for questionnaire development, and the survey questionnaires were distributed to employees from the upstream as well as downstream, from general manager to executive level to rank core competencies and competitive advantages with respect to financial and strategic performance. The survey results were analysed using Analytic Hierarchy Process (AHP), a mathematical model, and is synthesised using Super Decisions software. The study finds that there is a relationship between core competencies, competitive advantages and financial and strategic performance. The study also finds that core competencies have a relationship with competitive advantages where core competencies enable the company to have competitive advantages. The study ranks the identified core competencies with respect to competitive advantages as well to financial and strategic performance in the Malaysian National Oil Company. Of the core competencies, Operational Knowledge and Skills emerge on top when evaluated as a whole, with respect to competitive advantage, financial performance and strategic performance. Strategic Initiative is ranked second, and Talent Management is ranked third. The very bottom is Managing an Integrated O&G Company. Keywords: Analytic Hierarchy Process. core competencies, competitive advantages, financial performance, Malaysian National Oil Company, prioritisation, strategic performance, Super Decisions.